Modelling of Muscle Force Distributions During Barefoot and Shod Running - Sinclair, Jonathan (J Hum Kinet, 2015)
Research interest in barefoot running has expanded considerably in recent years, based around the notion that running without shoes is associated with a reduced incidence of chronic injuries. The aim of the current investigation was to examine the differences in the forces produced by different skeletal muscles during barefoot and shod running. Fifteen male participants ran at 4.0 m·s-1 (± 5%). Kinematics were measured using an eight camera motion analysis system alongside ground reaction force parameters. Differences in sagittal plane kinematics and muscle forces between footwear conditions were examined using repeated measures or Freidman’s ANOVA. The kinematic analysis showed that the shod condition was associated with significantly more hip flexion, whilst barefoot running was linked with significantly more flexion at the knee and plantarflexion at the ankle. The examination of muscle kinetics indicated that peak forces from Rectus femoris, Vastus medialis, Vastus lateralis, Tibialis anterior were significantly larger in the shod condition whereas Gastrocnemius forces were significantly larger during barefoot running. These observations provide further insight into the mechanical alterations that runners make when running without shoes. Such findings may also deliver important information to runners regarding their susceptibility to chronic injuries in different footwear conditions.